Unusual Adverse Effects of Immune Checkpoint Inhibitors: Autonomic Neuropathy, Palmoplantar Keratoderma, Reiter Syndrome & Myasthenia Gravis: A Case Series and Review of the Literature - Shalata, Walid; Yakobson, Alexander; Massalha, Ismaell; Y. Cohen, Aharon; Goldstein, Iris M.; Gibbs, Rachel; Omar, Abu Saleh; Asla, Mohnnad; Dudnik, Yulia; Abu-Juma'a, Ali; Peled, Nir; Rouvinov, Keren (International Journal of Innovative Research in Medical Science, 2020)
The immune checkpoint inhibitors (ICIs) have transformed the standards of care in cancer treatment and has dramatically improved patient prognoses. As a result of the introduction of these novel treatments several types of adverse events related to ICIs (immune related adverse events ((irAEs)) have been observed and reported. In this case series we describe the clinical course of four patients, with unusual ICI induced toxicities. The first patient was a 59 year-old female who received chemo-immunotherapy (pembrolizumab) for stage 4- lung adenocarcinoma, and developed autonomic neuropathy (AN). The second and third patients were both 63 year-old males who also received chemo-immunotherapy (pembrolizumab) for stage 4-A lung adenocarcinoma. One of those patients developed palmoplantar keratoderma and one developed conjunctivitis, urethritis and arthritis (Reiter syndrome). The fourth patient was an 80 year-old male who received chemo-immunotherapy (pembrolizumab) for stage 3-A squamous cell carcinoma of the lung and developed myasthenia gravis.